2020
DOI: 10.1007/s10548-020-00789-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Automatic Localization of the Irritative Zone Through Magnetic Source Imaging

Abstract: The present work aims at validating a Bayesian multi-dipole modeling algorithm (SESAME) in the clinical scenario consisting of localizing the generators of single interictal epileptiform discharges from resting state magnetoencephalographic recordings. We use the results of Equivalent Current Dipole fitting, performed by an expert user, as a benchmark, and compare the results of SESAME with those of two widely used source localization methods, RAP-MUSIC and wMNE. In addition, we investigate the relation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…First of all, the same dataset used here was used in [25], where an exemplar analysis with three ESI methods (MNE, ELOR and DSPM) was performed. Here, we considerably extended the comparison to include also more recent methods: noteworthy, we observed that recent methods such as SSM and MxNE do outperform older ones, hereby confirming recent results [19, 15]. In addition, we studied the impact of regularization and depth weighting parameters more in detail, highlighting similarities and differences between different methods.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…First of all, the same dataset used here was used in [25], where an exemplar analysis with three ESI methods (MNE, ELOR and DSPM) was performed. Here, we considerably extended the comparison to include also more recent methods: noteworthy, we observed that recent methods such as SSM and MxNE do outperform older ones, hereby confirming recent results [19, 15]. In addition, we studied the impact of regularization and depth weighting parameters more in detail, highlighting similarities and differences between different methods.…”
Section: Discussionsupporting
confidence: 82%
“…Another study that relates quite directly to our current study is that in [19], where the authors compared retrospectively SSM, RAP and wMNE with the results of an ECD analysis on epileptic subjects; indeed, also in this case the reference source is a point source, even though in this case it is the product of a former analysis and not a true source; anyway, the authors find MNE to be the least accurate and SSM the most accurate.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In recent years, similar Bayesian iterative approaches have been applied to this problem in order to develop semi-automated algorithms for clinical use. For example, an automated multidipole iterative Monte Carlo approach called “SESAME” was evaluated by Luria et al ( 2020 ) and was concordant with standard ECD fitting done by experienced staff. Pellegrino et al ( 2018 ) applied the coherent Maximum Entropy of the Mean (cMEM) to yield distributed magnetic source images (dMSI) that provided improved accuracy compared to ECD, also having the advantage of user-independent results; as dMSI results provide spatial and temporal voxelwise information, they can offer information about anatomic extent of source beyond that available from ECD.…”
Section: Discussionmentioning
confidence: 99%
“…These have included, for example, the application of the coherent Maximum Entropy of the Mean (cMEM) approach as described in Chowdhury et al (2013) to the localization of IEDs, a method termed distributed magnetic source imaging or dMSI, and found to be successful in comparison to ECD fitting by Pelligrino et al (2018). Recently, the Bayesian multidipole iterative Monte Carlo approach "SESAME" described by Sommariva and Sorrentino (2014) was evaluated in comparison to standard ECD methods by Luria et al (2020) for the localization of IEDs, likewise showing excellent performance. These methods were also noted to be advantageous because results were more operator-independent.…”
Section: Introductionmentioning
confidence: 99%